Educação profissional e qualificação do trabalhador : o caso do curso técnico em Telecomunicações do SENAI de Uberlândia - Alcantara, Jânio de Souza (2005)
The formation and the control of the manpower were challenges, constantly put back in the historical process of construction and consolidation of the capitalist system. Renewed to each crisis, this challenge was placed with great intensity due to the difficulties of accomplishment of the accumulation of the capital in crucial moments of the century XX. It was like this it in the world crisis that had as apex Second World War, one of the principal factors that fomented the industrialization process in Brazil. As, also, it was it in the wide productive restructuring, beginning a partner-historical process, unchained by the crisis of the petroleum in the beginning of the decade of 1970. Such a process reached in a structural mode the whole capitalist system in a, taking to deep changes in the production, materialized in an intensive application of the new technologies microeletronics in the production, in the innovative forms of administration of the work in a pattern powder-fordista, articulate with neoliberals politics, tuned with the globalization of the financial capital. This process was configured in an offensive of the capital in relation to the work, that it disembogued with larger intensity in Brazil, in the nineties. Erect Senai, in 1942, in the beginning of the process of Brazilian industrialization, in a context of demands for the workers' new qualifications was also intensely reached by the productive restructuring of the end passed century, as well as for the managerial culture of him engendered. The Technical course of Telecommunications of Senai of Uberlândia, interferes in that process. Because, with base in a methodology founded in the historical materialism dialectic, this work intends to do a reflection on the context, the genesis, the historical process, the unfoldings and the changes in the system of vocational education of Senai, and your interfaces with the world of the work. Taking as empiric base the case of the technical course of telecommunications of Senai of Uberlândia and the tissue of relationships that settled down to materialize it.